Professional Issues for Primary Teachers. - Browne, Ann (1-Off Ser., 2004)
This text has been written by: primary PGCE tutors; practising primary teachers; head teachers; and practitioners doing educational research. The book deals with the key professional issues faced by students on teacher training courses and practising primary teachers. Each chapter offers practical suggestions and in-depth discussion of essential topics.